Evaluation of antibacterial and antioxidant activity of extracts of endophytic fungi isolated from Indonesian Zingiberaceous plants - PRAPTIWI PRAPTIWI; KARTIKA DIAH PALUPI; AHMAD FATHONI; DEWI WULANSARI; MUHAMMAD ILYAS; ANDRIA AGUSTA (Nusantara Bioscience, 2016)
Abstract. Praptiwi, Palupi KD, Fathoni A, Wulansari D, Ilyas M, Agusta A. 2016. Evaluation of antibacterial and antioxidant activity of extracts of endophytic fungi isolated from Indonesian Zingiberaceous plants. Nusantara Bioscience 8: 306-311. Thirty-two endophytic fungi isolated from rhizome of six species of Zingiberaceae from Karanganyar, Central Java, Indonesia. Based on their morphological characters, all of endophytic isolates were classified into 10 genera. All of endophytic fungi isolates were then cultivated into 200 mL of Potato Dextrose Broth and incubated at room temperature. After three weeks, each of the fungi cultures was extracted with appropriate amount of ethyl acetate, and dried under reduced pressure. The extracts then evaluated for DPPH antioxidant activity and antibacterial activities against Escherichia coli Ina-CC B5 and Staphylococcus aureus Ina-CC B4 based on non-eluted TLC bioautography assays. The results showed 19 extracts are possessing antioxidant activity, 23 extracts inhibit the growth of E. coli Ina-CC B5, and 19 extracts inhibit the growth of S. aureus Ina-CC B4. The minimum inhibitory concentration (MIC) value of active extracts against S. aureus was in the range of 80-1280 ug/mL, while MIC against E. coli was in the range of 80->1280 ug/mL. The IC50 of active extracts were in the range of 50.97-2031.26 ppm. Further analysis by the eluted TLC-bioautography assay of active extracts showed that several fungal metabolites on active extract responsible for its/their bioactivity. It can be concluded that endophytic fungi isolated from Zingiberaceae can be used as new antibacterial and antioxidant resources.